Priorities for ensuring financial security of enterprises in the conditions of increased risk of doing business - Zakharova, Natalia; Захарова, Наталя Юріївна; Захарова, Наталья Юрьевна; Mazurova, I. (My University, 2021)
The article considers the consequences of the spread of COVID-19 and the introduction of quarantine restrictions for the economic security of the country, substantiates the need for an effective system of state regulation of the economy and timely business support, highlights the basic principles of financial security in uncertainty.
Keywords: financial security; enterprise; risk; threat; ease of doing business; economic and social development; insolvency